PELATIHAN OLAHDATA PENELITIAN BERBASIS TEKNOLOGI - Sahban, Muhammad Amsal; Aina, Mia; Indriani, Lely; Suryati, Suryati; Saifullah, Saifullah; Rahardian, Rifky Lana (Universitas Pahlawan Tuanku Tambusai, 2024)
Kegiatan pengabdian masyarakat dengan judul